2018
DOI: 10.1002/ange.201712435
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Dearomatization of Indolyl Dihydropyridines through an Enamine Isomerization/Spirocyclization/Transfer Hydrogenation Sequence

Abstract: Ah ighly efficient synthesis of enantioenriched spiroindolines by catalytic asymmetric dearomatization of indolyl dihydropyridines through ac hiral phosphoric acid catalyzede namine isomerization/spirocyclization/transfer hydrogenation sequence has been developed. This reaction proceeds under mild reaction conditions,a ffording novel spiroindolines in good yields (up to 88 %) with excellent enantioselectivity (up to 97 %e e). DFT calculations provide insights into the reaction mechanism as well as the origin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 88 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…In recent years, ynones of this type have emerged as valuable precursors for the preparation of a diverse array of molecular scaffolds. 3 6 For example, our groups and others have shown that the activation of the alkyne moiety of 1 promotes efficient dearomatizing spirocyclization 7 , 8 to form medicinally important spirocyclic indolenines 2 ; 9 , 10 this is most commonly done using π-acidic catalysts (especially Ag(I) species), although Brønsted acids, palladium(II) complexes, and electrophilic halogenation reagents can also be used ( 1 → 2 , Scheme 1 a, step 1). 3 , 11 , 12 Our groups have also shown that dearomatization works well on 2-halogenated indoles (i.e., 1 where X = Cl, Br or I) and that the resulting indoleninyl halide products (i.e., 2 where X = Cl, Br or I) can be transformed further via reaction with nucleophiles, or via Pd-catalyzed cross-coupling, to substitute the halide for various other groups ( 2 → 3 , Scheme 1 a, step 2).…”
mentioning
confidence: 99%
“…In recent years, ynones of this type have emerged as valuable precursors for the preparation of a diverse array of molecular scaffolds. 3 6 For example, our groups and others have shown that the activation of the alkyne moiety of 1 promotes efficient dearomatizing spirocyclization 7 , 8 to form medicinally important spirocyclic indolenines 2 ; 9 , 10 this is most commonly done using π-acidic catalysts (especially Ag(I) species), although Brønsted acids, palladium(II) complexes, and electrophilic halogenation reagents can also be used ( 1 → 2 , Scheme 1 a, step 1). 3 , 11 , 12 Our groups have also shown that dearomatization works well on 2-halogenated indoles (i.e., 1 where X = Cl, Br or I) and that the resulting indoleninyl halide products (i.e., 2 where X = Cl, Br or I) can be transformed further via reaction with nucleophiles, or via Pd-catalyzed cross-coupling, to substitute the halide for various other groups ( 2 → 3 , Scheme 1 a, step 2).…”
mentioning
confidence: 99%